An introduction to English morphology - Carstairs-McCarthy, Andrew (Edinburgh University Press, 2002)
Includes bibliographical references (p. 148-149) and index.; The book explores the implications of these different approaches to words in English. It is explains the various ways in which words are related to one another, and shows how the history of the English language has affected word structure. Topics include: words, sentences and dictionaries; a word and its parts (roots and affixes); a word and its forms (inflection); a word and its relatives (derivation); compound words; word structure; productivity; and the historical sources of English word formation